2010
DOI: 10.1111/j.1461-0248.2010.01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Assembly history dictates ecosystem functioning: evidence from wood decomposer communities

Abstract: Community assembly history is increasingly recognized as a fundamental determinant of community structure. However, little is known as to how assembly history may affect ecosystem functioning via its effect on community structure. Using wood-decaying fungi as a model system, we provide experimental evidence that large differences in ecosystem functioning can be caused by small differences in species immigration history during community assembly. Direct manipulation of early immigration history resulted in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
513
8
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 534 publications
(543 citation statements)
references
References 52 publications
(113 reference statements)
20
513
8
2
Order By: Relevance
“…The stochasticity of wood colonisation, i.e. the 'who comes first' effect, may also be an important determinant of community composition and decay activity (Valaskova et al 2009;Fukami et al 2010;Dickie et al 2012).…”
Section: Drivers Of Decomposer Activitymentioning
confidence: 99%
“…The stochasticity of wood colonisation, i.e. the 'who comes first' effect, may also be an important determinant of community composition and decay activity (Valaskova et al 2009;Fukami et al 2010;Dickie et al 2012).…”
Section: Drivers Of Decomposer Activitymentioning
confidence: 99%
“…The destruction of assembled communities by disturbances precludes the dominance of equilibrium-based mechanisms of coexistence, which will strongly affect biodiversityecosystem functioning relationships [55], because the dominance of species will not only be based on their resource use or effect traits [56], but also by chance, e.g. through priority effects in the colonization sequence [57,58]. If successful, functional traits in non-equilibrium conditions are not related to the use of resources and growth, but to colonization and dispersal abilities, or the ability to withstand disturbances.…”
Section: Issue (2): Non-equilibrium Biodiversity and Ecosystem Functimentioning
confidence: 99%
“…The priority effects in dead wood communities found in our and previous studies (Fukami et al. 2010; Weslien et al. 2011; Dickie et al.…”
Section: Discussionmentioning
confidence: 99%
“…Short‐term experimental studies have shown that manipulating arrival order of species can strongly affect not only species composition and richness, but also ecosystem function (Fukami et al. 2010; Dickie et al. 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation